Improvement of die and roller changing method of a poultry feed processing industry - Iqbal, M.; Iqbal, Salma A.; Alam, Md. Zahangir (2011)
Productivity is a very important concern now a day for an industry. Productivity improvement is a vital factor for continuous economic growth and increase in standard of living. Productivity can be improved through time and motion study. Time and motion study plays a very important role to improved productivity of an industry or any production sector where human hand plays a very important role. Time and motion study reduce production time and cost. It also increases human efficiency in the industry. So the implementation of time and motion study in any production sector is very important. This paper describes the improvement of productivity of two pallet mills using time and motion study in a poultry feed mill. The paper discusses (i) the existing method of die and roller changing method, (ii) implementing of the new method, (iii) result analysis and (iv) benefits of using the modified method for changing die and roller and only die of the poultry feed mill. Lastly recommendations for the management of the firm